Factors influencing the relevance of air quality in the attractiveness of a tourism destination: Differences between nature-based and urban destinations. (October 2022) - Eusébio, Celeste; Carneiro, Maria João; Rodrigues, Vitor; Robaina, Margarita; Madaleno, Mara; Gama, Carla; Oliveira, Kevin; Monteiro, Alexandra
Abstract: Assessing tourism destination attractiveness is a dynamic procedure influenced by constantly changing factors. Despite the existence of various studies on destination attractiveness, less attention has been devoted to measuring the relevance of air quality. The growing concerns related to the impacts of air pollution worldwide, make it imperative to develop attractiveness models which incorporate air quality. Based on survey data collected from 625 visitors, this study examines the importance of air quality when selecting tourism destinations and the factors influencing it. Findings reveal a moderate importance of air quality when selecting tourism destinations, with pro-environmental behaviors at home, perception of the destination's air quality, age, and visitor origin being the most influential factors. The results show that air quality has higher importance when visiting nature-based destinations. Highlights: Air quality is a relevant attribute for the selection of tourism destinations The relevance of air quality is higher in nature-based destinations Sustainable behaviors and air quality perception influence the relevance of air quality in destinations' choice The study offers valuable insights to include air quality in destinations' attractiveness models